2021
DOI: 10.3390/horticulturae7110442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Soil and Ripening Stage in Capsicum chinense var. Jaguar on the Content of Carotenoids and Vitamins

Abstract: The purpose of this work was to investigate the effect of the ripening stage and type of soil on the concentration of carotenoids and vitamins in Habanero pepper (Capsicum chinense Jacq.). Pepper plants were grown in two soils named according to the Mayan classification as: K’ankab lu’um (red soil) and Box lu’um (black soil). The results of two harvests at 320 and 334 PTD (post-transplant day) showed that the ripening stage exhibited a significant effect (p < 0.05) on the concentration of carotenoids and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…On the other hand, the degree of ripeness has been shown to influence the synthesis of secondary metabolites in previous studies [12]. The results of this study indicate that this factor also affects the concentration of the volatile compounds in the Habanero pepper.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the degree of ripeness has been shown to influence the synthesis of secondary metabolites in previous studies [12]. The results of this study indicate that this factor also affects the concentration of the volatile compounds in the Habanero pepper.…”
Section: Discussionsupporting
confidence: 52%
“…The content of metabolites such as capsaicinoides, vitamins, carotenoids and polyphenols in the Habanero pepper is mainly related to the degree of ripeness, the type of soil, and the genetic variety of the pepper [10][11][12]. Previous works have reported only the effect of the genetic variety and degree of ripeness on the profile and concentration of volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was observed that plants cultivated in black soils presented a notably higher TPC (217.13 ± 28.04 mg GAE/100 g dry pepper) and AC (86.51 ± 0.82% inhibition) compared with those grown in other soil types, including red soil (135.17 ± 14.24 mg GAE/100 g dry pepper, with inhibition below 86%) and brown soil, which displayed intermediate behavior [54]. This study suggests that these differences were primarily attributed to variations in electrical conductivity, organic matter content, and increased nitrogen presence [55,56]. Overall, such factors are thought to impact nutrient availability and uptake in plants, ultimately modulating the polyphenol content and thereby the AC of the products.…”
Section: Discussionmentioning
confidence: 80%
“…93 Vitamin C and E levels increased to a maximum of 119.44 ± 4.72 mg 100 g −1 DW and 9.69 ± 0.02 mg 100 g −1 DW at 334 days after transplant (DAT) while carotenoid content decreased from 320 to 334 DAT in C. chinense "Habanero". 94…”
Section: Ripening-related Changes In Secondary Metabolites In Capsicummentioning
confidence: 99%
“…Fluorescence spectra of chili fruit exocarp showed a decline in the chlorophyll (685 and 730 nm) levels in the mature green fruits and increase in the carotenoids (490 to 580 nm), β-carotene, in the preripe and capsanthin in the ripe fruits, respectively . Vitamin C and E levels increased to a maximum of 119.44 ± 4.72 mg 100 g –1 DW and 9.69 ± 0.02 mg 100 g –1 DW at 334 days after transplant (DAT) while carotenoid content decreased from 320 to 334 DAT in C. chinense “Habanero” …”
Section: Ripening-related Changes In Secondary Metabolites In Capsicummentioning
confidence: 99%